Local levels of inflammatory mediators in uncontrolled type 2 diabetic subjects with chronic periodontitis. (11th November 2013) - Duarte, Poliana M.; Bezerra, Joyce P.; Miranda, Tamires S.; Feres, Magda; Chambrone, Leandro; Shaddox, Luciana M.
Abstract Aim The aim of this study was to evaluate the levels of a wide panel of cyto/chemokines in the gingival crevicular fluid (GCF) of uncontrolled type 2 diabetic subjects as compared with non‐diabetic subjects with periodontitis. Methods Twenty‐six uncontrolled type 2 diabetic subjects (glycated haemoglobin levels >7.5%) and 20 non‐diabetic subjects with chronic periodontitis were enrolled in this study. The levels of 14 cyto/chemokines were measured in the GCF of healthy and diseased sites of the diabetic and non‐diabetic subjects using multiplex bead immunoassays. Results The concentrations of eotaxin, macrophage inflammatory protein‐1α, granulocyte‐macrophage colony‐stimulating factor, interleukin (IL)‐6, tumour necrosis factor‐α and IL‐12 were higher in healthy and diseased sites of diabetic than non‐diabetic subjects, after adjustment for multiple comparisons (p < 0.0035). Conclusion Uncontrolled type 2 diabetes mellitus modulated the local levels of several cyto/chemokines at both healthy and diseased periodontal sites in favour of a proinflammatory profile, which may partially explain the greater susceptibility of diabetic subjects to periodontal breakdown.